80 Importance of 3D Tee in Procedure Success of Percutaneous Paravalvular Leak Closure. (31st May 2014) - Rekhraj, S; Hoole, SP; McNab, D; Densem, C; Boyd, J; Parker, K; Shapiro, LM; Rana, BS
Abstract : Purpose: Paravalvular leaks (PVL) are a recognised complication post surgery, but rarely result in heart failure and haemolysis. Redo surgery may present technical challenges and is associated with significant morbidity and mortality. Percutaneous repair (PR) of PVL has been shown to be a credible alternative. 3D TEE imaging has been shown to improve patient selection and facilitate procedural success. Methods: Consecutive PVL patients treated with PR at our institution between May 2010 to November 2013 were studied. All procedures were guided using fluoroscopy and 3D transoesophageal echocardiography (TEE). Live 3D colour datasets and Xplane TEE imaging were used to accurately locate and measure PVL defects, guiding device sizing. Results: 29 patients (mean age 70 years, range 45–91, 66% male, logistic Euroscore 26.8 ± 16%) underwent 31 PVL closure procedures: 22 (76%) were aortic position and 7 (24%) mitral position. 16 (55%) were mechanical valves. PVL severity was defined 0 = none, 1 mild, 2 moderate 3 = severe. All patients had ≥2+ PVL severity.In 20 patients >1 PVL was found. Average defect size 5mm (range 3–10mm). Aetiology of PVL were heavy calcification (n = 24) and previous endocarditis (n = 5). Indications for leak closure included heart failure only (n = 13), haemolysis only (n = 8) or both (n = 8). 4 patients needed 2 devices. Amplatzer Vascular Plug III devices were used in all cases. Deployment of PVL closure device was unsuccessful in 4, with 3 due to complex defects which could not be crossed and 1 defect was too large. Procedure and fluoroscopy times were 125 ± 65 mins and 32.8 ± 27.7 mins respectively. Procedure complications included access site complications (n = 4), pacemaker insertion (n = 1) and iatrogenic aortic root dissection (n = 1). There were no procedure related deaths. Follow up data was available in 22 patients (average 8 months). Successful PVL closure (defined as ≤ 1+ residual regurgitation) was achieved in all but 2 patients. There was an improvement in: haemolysis (8 patients); symptoms (11 patients, NYHA class of ≥ 1 grade) and heart failure (13 patients). Two patients needed redo cardiac surgery with 1 due to failed PVL closure and 1 due to another significant PVL. Conclusions: Percutaneous PVL closure is a feasible and safe alternative to high risk redo cardiac surgery. 3D TEE plays a crucial role in defining anatomy, defect sizing and procedure guidance. Thereby, reducing both procedure and fluoroscopy times (compared to published data) and may improve patient selection.